OnabotulinumtoxinA decreases interictal CGRP plasma levels in patients with chronic migraine. Issue 5 (May 2015) - Cernuda-Morollón, Eva; Ramón, César; Martínez-Camblor, Pablo; Serrano-Pertierra, Esther; Larrosa, Davinia; Pascual, Julio
Abstract : Abstract: OnabotulinumtoxinA (onabotA) has shown efficacy in chronic migraine (CM). Its mechanism of action, however, remains obscure. We have analysed whether treatment with onabotA is able to induce changes in interictal plasma calcitonin gene-related peptide (CGRP) concentrations, which have been shown to be increased in patients with CM. Calcitonin gene-related peptide levels were determined in samples obtained from the right antecubital vein using ELISA, outside a migraine attack and having taken no symptomatic medication in the previous 24 hours, in 83 patients with CM (average age 44 years; 94% females) before and 1 month after treatment with 155 to 195 U of onabotA. CGRP levels after onabotA treatment (median, 51.89 pg/mL; range, 199.4-10.2) were significantly lower as compared with CGRP levels obtained before onabotA treatment (median, 74.09 pg/mL; range, 241.0-11.4; P = 0.001). Pretreatment CGRP levels in responders (76.85 pg/mL) were significantly higher than those seen in nonresponders (50.45 pg/mL; P = 0.001). One month after treatment, the CGRP levels did not change in nonresponders (51.89 pg/mL; P not significant), but significantly decreased in responders (52.48 pg/mL; P = 0.003). A number of demographic factors, clinical features, and comorbidities were not different in responders as compared with those of nonresponders. These results confirm that interictal CGRP levels can be of help in predicting the response to onabotA and suggest that the mechanism of action of onabotA in CM is the reversal of sensitization as a result of the inhibition of CGRP release. Abstract : Plasma CGRP levels decrease in patients with chronic migraine responding to onabotulinumtoxinA.